A pilot assessment of the career and job satisfaction of the pharmaceutical workforce in Lebanon - Elsa Nassar; Sibelle Kassouf; Aline Hajj; Hala Sacre; Marwan Akel; Rony M. Zeenny; Chadia Haddad; Pascale Salameh (Taylor & Francis Group, 2022)
Background Lebanon has been recognized as a center for high-quality healthcare services in the Middle East because of its prestigious facilities certified by international bodies, competent health workers, and credible pharmaceutical sector. This study assessed the professional situation of the Lebanese pharmaceutical workforce upon graduation and entry to the job market. It also evaluated the satisfaction of pharmacists with the financial, physical, and psychological aspects of their job and the effect of the current socioeconomic crisis on their profession. Methods A cross-sectional study was performed between January and May 2021 among 114 Lebanese pharmacists from all pharmaceutical sectors across Lebanon. A self-administered questionnaire was elaborated to assess the pharmaceutical workforce in Lebanon. The online questionnaire was built using Google Forms and disseminated via emails and social platforms. Results Fresh graduates seemed more oriented toward community pharmacies, and 78.1% of the participants worked at least once in their lifetime in a community pharmacy. Pharmacists from the public university worked predominantly in the community pharmacy sector, while those who graduated from private universities worked mainly as medical representatives. Hospital pharmacy comprised significantly more PharmD graduates than other sectors; medical representatives had mainly a BS pharmacy, while those working as industrial pharmacists had a Master's degree. A low percentage (31.6%) of participants found it easy to get hold of a job across different pharmaceutical sectors while 64.0% considered the internships experience insufficient to get employed. Nearly half (48.2%) of the respondents were poorly satisfied with their job, and 54.0% of community pharmacists reported not working in their preferred field compared to 39.1% of pharmacists from other sectors. Also, 65.79% felt that the economic crisis and the consequent medication shortages affected their credibility and how society perceived them. About half (45.61%) of the participants reported that their employment status was not affected by the crisis; the rest got a second job to cover their expenses (15.79%) or changed jobs (14.91%). Conclusion Our study findings revealed that most Lebanese fresh graduates worked as community pharmacists, which does not correspond to their preference, the available job market, and the modern pharmacy wingspan. Most pharmacists were also financially, physically, and emotionally dissatisfied due to the Lebanese economic crisis that added heavy workloads and responsibilities without any financial raise.